Productive break-even point and marketing margins of the jalapeño peppers producer (Capsicum annuum ‘jalapeño’) in Mexico - Sánchez-Toledano, Blanca; Góngora-Pérez, Rubén; López-Santiago, Marco; Cuevas-Reyes, Venancio (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
Farmers in Mexico are increasingly interested in higher-value alternatives to commodity production. The direct sales channel is a potentially attractive marketing alternative as it offers higher net income to farmers. However, in Mexico, few farmers use direct sales. The objective of this study, was to estimate the productive breakeven point and the marketing margins of the jalapeño pepper production in order to obtain profitability for the producers of this vegetable in Quintana Roo, Mexico. A sampling for finite populations was carried out, and the sample size was 89 producers. Results showed that a minimum of 10,754.5 kg.ha-1 is required with a rural sale price no less than 5.6 $.kg-1 of jalapeño pepper (equivalent to $0.20), to maintain a profitable and sustainable commercial supply of the crop. Producers sold most of their jalapeño production to wholesalers (58.4%), despite results showed the fact, that direct markets are the most profitable marketing channel for farmers of the area. The gross marketing margin was 74.5%, which indicated that, by each peso paid for jalapeño consumers, 74 cents corresponded to the intermediation process, and 25 cents to the producer. The organization of producers is crucial to increase the quality of the product and for a greater presence in the marketing chain.